2022
DOI: 10.1038/s41586-021-04311-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal imaging of dust hiding the black hole in NGC 1068

Abstract: Publisher's note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…where M dust is the dust mass, T dust is the dust temperature, κν is the dust emissivity (∼ κ352GHz × (ν [GHz]/352) β with κ352GHz = 0.09m 2 kg −1 ), β is the emissivity index, and DL is the luminosity distance. We note that the infrared interferometer, GRAVITY, has revealed the existence of hot dust near the black hole (GRAVITY Collaboration et al 2020;Gámez Rosas et al 2022). However, this hot dust does not contribute to the ALMA high-frequency observation.…”
Section: Multiple Componentsmentioning
confidence: 84%
See 1 more Smart Citation
“…where M dust is the dust mass, T dust is the dust temperature, κν is the dust emissivity (∼ κ352GHz × (ν [GHz]/352) β with κ352GHz = 0.09m 2 kg −1 ), β is the emissivity index, and DL is the luminosity distance. We note that the infrared interferometer, GRAVITY, has revealed the existence of hot dust near the black hole (GRAVITY Collaboration et al 2020;Gámez Rosas et al 2022). However, this hot dust does not contribute to the ALMA high-frequency observation.…”
Section: Multiple Componentsmentioning
confidence: 84%
“…One possible radiation mechanism to explain the centimeter/submillimeter spectrum (figure 1) by a single flatspectrum component (see also Gámez Rosas et al 2022) assuming that flux rise/fall in > 10 GHz is due to beamsize effects is free-free emission and self-absorption. The specific luminosity regarding free-free emissions at frequency ν is…”
Section: Single Component (Free-free)mentioning
confidence: 99%
“…Indeed, the obscuring material around the galaxy's central engine has been the subject of intense study for the past few decades. The nuclear region has been examined in the radio with Very Long Baseline Interferometry from the Very Large Array and in the infrared using interferometry from the Very Large Telescope to glean insight into the distribution, composition, and thermal properties of the obscuring material (van der Hulst et al 1982;Greenhill et al 1996;Rottgering et al 2004;Gámez Rosas et al 2022).…”
Section: Ngc 1068 and Observationsmentioning
confidence: 99%
“…with GRAVITY (GRAVITY Collaboration et al 2017), have revealed that (somewhat colder) torus dust can be significantly entrained along the polar axis (López-Gonzaga et al 2016;Hönig & Kishimoto 2017). The presence of a small amount of optically-thin hot dust is therefore plausible in principle for luminous quasars (but see GRAVITY Collaboration et al 2020a,b for the lack of such an effect in fainter AGN, and see also results from the Matisse instrument revealing more complicated dust distribution in Gámez Rosas et al 2022).…”
Section: More Complicated Dust Modelsmentioning
confidence: 99%